2021
DOI: 10.1111/hex.13350
|View full text |Cite
|
Sign up to set email alerts
|

Children's perspectives and experiences of the COVID‐19 pandemic and UK public health measures

Abstract: Background:The COVID-19 pandemic has had profound impacts on how we live our lives; yet, the implications for children and the effects on children's everyday lives have been relatively underacknowledged. Understanding children's views on COVID-19 and related restrictions on their lives provides an important opportunity to understand how children have responded to the pandemic, including the impacts on their social and emotional well-being.Objective: This study explored the experiences and perspectives of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…Recently published research shows that parents report smaller declines in the psychological wellbeing of adolescents, compared to children under 11 [ 11 ]. These differences may be elucidated by a recent study with younger children (7–11) which highlighted that these pre-adolescent children expressed sadness and fear of their family and friends being at risk of dying from COVID-19 [ 12 ]. In contrast, young people 12–17 years have reported that the greatest impacts of the pandemic have been disruption to their learning because of school closures and limited face-to-face interaction with their social networks [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently published research shows that parents report smaller declines in the psychological wellbeing of adolescents, compared to children under 11 [ 11 ]. These differences may be elucidated by a recent study with younger children (7–11) which highlighted that these pre-adolescent children expressed sadness and fear of their family and friends being at risk of dying from COVID-19 [ 12 ]. In contrast, young people 12–17 years have reported that the greatest impacts of the pandemic have been disruption to their learning because of school closures and limited face-to-face interaction with their social networks [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of COVID-19, an abundance of information about infection and transmission risks and related measures to contain the pandemic has been addressed to the public, including children (Provenzi et al, 2020;Thompson et al, 2021;Zou and Tang, 2021). Most countries have imposed restrictive measures and broadcasted campaigns involving visual and verbal slogans to promote citizen observance of safe behavior (Berasategi et al, 2020;Bray et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…For any teaching intervention or information campaign to be meaningful to them, it is crucial that it starts from their point of view. It is therefore of great importance to gain insight into children's understanding of the novel coronavirus and ways of responding to the crisis (Thompson et al, 2021). Such insight would allow the selection and formulation of age-appropriate and accurate explanations and representations that they could meaningfully handle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations